Fecal ingestion rate based on worker activity patterns during stool handling in a ruminant farm - Paramitadevi, Yudith V.; Priadi, Cindy R.; Rahmatika, Iftita; Rukmana, Andriansjah (Narra Sains Indonesia, 2025)
Farm workers who handle livestock stools face an increased risk of infection by pathogenic bacteria, such as Escherichia coli O157 and Salmonella spp., leading to millions of severe health issues and thousands of fatalities annually. The aim of this study was to assess the impact of these pathogens by measuring their concentrations, determining rates of unintentional fecal consumption, and conducting a quantitative assessment of microbial risk. An integrated farm in Sukabumi City, Indonesia, was examined for E. coli O157 and Salmonella spp. in livestock stools. Additionally, the study monitored the rate of incidental fecal ingestion among farm workers. Stool samples were collected (n= 40) from ruminants and analyzed following ISO 16649-1:2018, ISO 9308-1:2014, and ISO 6579-1:2017/Amd.1:2020. The study tracked worker’s behavior daily to determine the contact time. The fecal ingestion rate was calculated by multiplying the estimated stool weight ingested by the contact time workers spent cleaning livestock stools in the barn each day. Microbial analysis revealed that the highest concentration of E. coli O157 in beef cattle stools was 2.49 log10 CFU/g. The study determined mean fecal ingestion rates during the dry season (8.64 mg/day) and rainy season (6.84 mg/day). Results from the quantitative microbial risk assessment showed that stool from beef cattle posed a higher risk of E. coli O157 infection compared to other ruminants, with an estimated disease burden of 9.8 × 10-3 pppy. This study represents the first comprehensive quantitative evaluation of fecal ingestion by farm workers during animal husbandry. The findings underscore the need for improved worker safety measures, such as enhanced sanitation practices and protective equipment, to mitigate the risks of handling livestock stools.